Risk of ESRD in prior living kidney donors. Issue 5 (8th March 2018) - Wainright, Jennifer L.; Robinson, Amanda M.; Wilk, Amber R.; Klassen, David K.; Cherikh, Wida S.; Stewart, Darren E.
Abstract : We studied End‐Stage Renal Disease (ESRD) in living kidney donors (LKDs) who donated in the United States between 1994 and 2016 (n = 123 526), using Organ Procurement and Transplantation Network and Centers for Medicare and Medicaid Services data. Two hundred eighteen LKDs developed ESRD, with a median of 11.1 years between donation and ESRD. Absolute 20‐year risk was low but not uniform, with risk associated with race, age, and sex and increasing exponentially over time. LKDs had increased risk of ESRD if they were male (adjusted hazard ratio [aHR]: 1.75, 95% confidence interval [95%CI]: 1.33‐2.31), had higher BMI (aHR: 1.34 per 5 kg/m 2, 95%CI: 1.10‐1.64) or lower estimated GFR (aHR: 0.89 per 10 mL/min, 95% CI: 0.80‐0.99), were first‐degree relatives of the recipient (parent: [aHR: 2.01, 95% CI: 1.26‐3.21]; full sibling [aHR: 1.87, 95%CI: 1.23‐2.84]; identical twin [aHR: 19.79, 95%CI: 7.65‐51.24]), or lived in lower socioeconomic status neighborhoods at donation (aHR: 0.87 per $10k increase; 95%CI: 0.77‐0.99). We found a significant interaction between donation age and race, with higher risk at older ages for white LKDs (aHR: 1.26 per decade, 95%CI: 1.04‐1.54), but higher risk at younger ages for black LKDs (aHR: 0.75 per decade, 95%CI: 0.57‐0.99). These findings further inform risk assessment of potential LKDs. Abstract : The 20‐year risk of end‐stage renal disease in living kidney donors is not uniform among donors, and donor socioeconomic status, eGFR, race, sex, relatedness to recipient, and age at donation are associated with risk of renal disease. See the companion article onpage 1140 from Matas et al, and an editorial from Gill onpage 1041 .